2007
DOI: 10.1007/s00248-006-9090-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Uptake by the Marine Sponge Aplysina aerophoba

Abstract: Sponges (Porifera) are filter feeders that take up microorganisms from seawater and digest them by phagocytosis. At the same time, many sponges are known to harbor massive consortia of symbiotic microorganisms, which are phylogenetically distinct from those in seawater, within the mesohyl matrix. In the present study, feeding experiments were performed to investigate whether phylogenetically different bacterial isolates, hereafter termed "food bacteria," microbial seawater consortia, and sponge symbiont consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 33 publications
4
118
0
1
Order By: Relevance
“…In the case of Vibrio anguillarum, the occurrence of a flagellum, which is likely to be beating within the choanocyte chambers during the process of phagocytosis, might well complicate the engulfing by the choanocytes. However, Wehrl et al (2007) reported that retentions rates of hyperflagellated and hypoflagellated Vibrio mutants were similar to that of the respective wild-type strain. Therefore, it has to be considered that choanocytes are actually able to discriminate bacteria by perceiving characteristic wall compounds, as suggested by Wehrl et al (2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of Vibrio anguillarum, the occurrence of a flagellum, which is likely to be beating within the choanocyte chambers during the process of phagocytosis, might well complicate the engulfing by the choanocytes. However, Wehrl et al (2007) reported that retentions rates of hyperflagellated and hypoflagellated Vibrio mutants were similar to that of the respective wild-type strain. Therefore, it has to be considered that choanocytes are actually able to discriminate bacteria by perceiving characteristic wall compounds, as suggested by Wehrl et al (2007).…”
Section: Discussionmentioning
confidence: 96%
“…However, a few studies have clearly demonstrated that at least some sponges may perform a size-independent selection of the ingested microbes (e.g. Frost 1976, 1980b, Van de Vyver et al 1990, Yahel et al 2006, Wehrl et al 2007). Likewise, the outcome of our experiment supports that feeding in Hymeniacidon perlevis is a selective process.…”
Section: Discussionmentioning
confidence: 99%
“…Sponge and microbial cell separations-Methods for cell separation were adapted from Wehrl et al (2007). Frozen sponge specimens (6 to 10 cm long) were thawed at 4uC, weighed to the nearest 0.01 g, and minced into small pieces using a sterile razor blade.…”
Section: Methodsmentioning
confidence: 99%
“…AR proteins have also been recently shown to be secreted by the intracellular pathogens Legionella pneumophila and Coxiella burnetii and to interfere with the microtubule-dependent vascular transport of host cells, hence blocking the normal progression of phagocytosis (Pan et al, 2008). As uptake of food bacteria by sponge cells is also mediated by phagocytosis (Wehrl et al, 2007), the sponge-specific AR and TPR proteins reported in this study could possibly represent a mechanism by which symbiotic bacteria avoid digestion, and could explain the long-standing question of how food and symbionts are discriminated by the sponge (Wilkinson et al, 1984).…”
Section: Bacteria-sponge Interaction Through Repeat Proteinsmentioning
confidence: 99%